2014
DOI: 10.1158/0008-5472.can-14-0993
|View full text |Cite
|
Sign up to set email alerts
|

PELP1 Overexpression in the Mouse Mammary Gland Results in the Development of Hyperplasia and Carcinoma

Abstract: Estrogen receptor coregulator over-expression promotes carcinogenesis and/or progression of endocrine related-cancers in which steroid hormones are powerful mitogenic agents. Recent studies in our laboratory, as well as others, demonstrated that the estrogen receptor coregulator PELP1 is a proto-oncogene. PELP1 interactions with histone demethylase KDM1 play a critical role in its oncogenic functions and PELP1 is a prognostic indicator of decreased survival in breast cancer patients. However, the in vivo signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Herein, we show that PELP1-cyto expression induces a multiacinar phenotype that is most similar to what has been observed with ErbB2 expression in MCF-10A cells (40). In a mouse model, mammary gland-specific PELP1 overexpression promotes hyperplasia and tumor formation of ER-positive carcinoma (12). A PELP1-cyto mammary gland specific mouse model has also been shown to induce hyperplasia and increase activation of Erk and Akt signaling (11).…”
Section: Pelp1 Signaling and Nf-b Activation-ikk/nf-b Signaling Issupporting
confidence: 73%
See 1 more Smart Citation
“…Herein, we show that PELP1-cyto expression induces a multiacinar phenotype that is most similar to what has been observed with ErbB2 expression in MCF-10A cells (40). In a mouse model, mammary gland-specific PELP1 overexpression promotes hyperplasia and tumor formation of ER-positive carcinoma (12). A PELP1-cyto mammary gland specific mouse model has also been shown to induce hyperplasia and increase activation of Erk and Akt signaling (11).…”
Section: Pelp1 Signaling and Nf-b Activation-ikk/nf-b Signaling Issupporting
confidence: 73%
“…Mutant PELP1 with an altered nuclear localization sequence results in a protein that is predominately cytoplasmic (PELP1-cyto) and leads to activation of cytoplasmic signaling in breast cancer cell line models (10). In mammary-specific transgenic mouse models, expression of wild-type PELP1 or PELP1-cyto induced mammary gland hyperplasia that was associated with increased Akt and Erk1/2 signaling (11,12). Cytoplasmic PELP1 signaling has primarily been studied in breast cancer cell line models and in vivo mouse models (10,11,13).…”
mentioning
confidence: 99%
“…Several reports have shown that PELP1 downregulation significantly reduced the proliferation, survival, migration, and invasion of cancer cells in multiple cancer types . Recently, we demonstrated that PELP1 overexpression contributes to mammary gland carcinoma using a tissue‐specific transgenic mouse model . PELP1 plays a role in ER‐positive metastases via extranuclear ER‐Src‐PELP1‐ILK1 pathway and knockdown of PELP1 reduced the invasion and metastasis of TNBC cells .…”
Section: Discussionmentioning
confidence: 80%
“…Overexpression of PELP1 in the mammary gland using transgenic mice model contributed to mammary gland carcinoma, further supporting its oncogenic potential in vivo (Cortez et al 2014). PELP1 oncogenic signaling is implicated in progression of several cancers including breast (Krishnan et al 2015; Zhang et al 2015), endometrial (Vadlamudi et al 2004) ovarian (Chakravarty 2008), salivary (Vadlamudi et al 2005a), prostate (Yang et al 2012), lung (Slowikowski et al 2015), pancreas (Kashiwaya et al 2010) and colon (Ning et al 2014).…”
Section: Functions Of Pelp1 In Cancermentioning
confidence: 91%
“…EGF can promote PELP1 phosphorylation at CDK sites (Olsen et al 2006). Studies using inducible transgenic mice model revealed that PELP1 regulates expression of a number of known ESR1 target genes involved in cellular proliferation including cyclin D1 and CDKs, and that PELP1 was hyper-phosphorylated at its CDK phosphorylation site, suggesting an autocrine loop involving the CDK–cyclin D1–PELP1 axis in promoting mammary tumorigenesis (Cortez et al 2014). …”
Section: Biological Functions Of Pelp1mentioning
confidence: 99%